1994
DOI: 10.1111/j.2044-8279.1994.tb01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension and interest in home reading

Abstract: This study was designed to provide information on how families from different sociocultural backgrounds help with reading at home, and shed light on the types of helping strategy which tend to be most successful. A further aim was to investigate possible mechanisms through which a home reading project might lead to significant reading gains. Parents from four main target groups were visited at home and interviewed about the help which family members gave with educational activities. The groups involved were mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(13 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The results revealed that middle-income children engaged in such activities more frequently than low-income children. This is consistent with many other studies showing that middle-income children have more exposure to books than low-income children (Bus, van Ijzendoorn, & Pellegrini, 1995;Scarborough & Dobrich, 1994), as well as recent evidence of income-related differences in exposure to rhyming activities (Chaney, 1994;Elliott & Hewison, 1994;Marvin & Mirenda, 1993). In our sample, African-American and European-American children of the same income level participated in relevant activities with about the same frequency.…”
Section: Discussionsupporting
confidence: 80%
“…The results revealed that middle-income children engaged in such activities more frequently than low-income children. This is consistent with many other studies showing that middle-income children have more exposure to books than low-income children (Bus, van Ijzendoorn, & Pellegrini, 1995;Scarborough & Dobrich, 1994), as well as recent evidence of income-related differences in exposure to rhyming activities (Chaney, 1994;Elliott & Hewison, 1994;Marvin & Mirenda, 1993). In our sample, African-American and European-American children of the same income level participated in relevant activities with about the same frequency.…”
Section: Discussionsupporting
confidence: 80%
“…(pp. 58-59) Many of the children in the present study had home contexts which, given their unfavourable socio-economic circumstances, were unlikely to provide rich experiences of this kind (Elliott & Hewison, 1994). Whether a greater focus upon story (or, for that matter, phonological processes) would have resulted in a greater impact upon the children's long-term reading performance was not possible to discern.…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, some parents, especially h s e from low-income backgrounds, tend, in their literacy interactions with their children, to give undue weight to skill development at the expense of enjoyment and entertainment (Baker et al, 1994;Elliott & Hewison, 1994;(Goldenberg et al, 1992). Formal instruction from parents may be counterproductive if it makes learning to read seem like work rather than play.…”
Section: Implications For Intervention and Guidance To Parentsmentioning
confidence: 95%